Še enkrat: Branko Rudolf lutkar - Glazer, Alenka (Otrok in knjiga, 1986)
This article continues the research of Rudolf's puppet-plays (conf. Otrok in knjiga = Child and the Book, No. 21). Recently found, still impublished puppet-play Konjiške gore zmaj (The Dragon of Konjiška gora, 1934) is based on motives from folk prose, but by an original figure of Gašperček and partly used archaic language predicts Rudolf's book of poems Žvegla potepuhova (Tramp's Flute, 1960).
Keywords: lutkovno gledališče; mladinska književnost; puppet-plays; youth literature